Budgetary balances adjustments from Governmental Accounting into National Accounts in EU countries: - Jesus, M.; Laureano, Raul M. S.; Jorge, S.M. (9th International EIASM Public Sector Conference, 2016)
Having a deficit limit, EU countries are compelled to attain such objective and therefore will eventually choice any instrument to reach its accomplishment. This paper argues that accounting discretion might be used by countries in managing adjustments made when translating data from Governmental Accounting (GA) into National Accounts (NA) as to window-dress their final deficit/surplus reported to EUROSTAT. Assuming that managing the final deficit could be every country’s aim, it shows that certain circumstances might facilitate the use GA-NA ‘adjustments discretion’.